Evaluation of physical and physiological characteristics of the Olympic champion Turkish deaf men`s national handball team - Gümüs, M.; Ele, S. (Journal of Education and Training Studies, 2018)
The aim of this study is to evaluate physical and physiological characteristics of the Olympic Champion Turkish Deaf Men`s National Handball Team. A total of 20 athletes participated in the study with age average of 27 ± 6.26 years, sports age average of 11.45±5.35 years, average height of 180.3±6.70 cm and an average body weight of 82.49±10.38 kg. In the evaluation of the data SPSS 19.0 program was used, frequency and distribution is observed, average standard deviation, maximum, and minimum values were taken. The average Body Mass Index (BMI) of the athletes were determined as 25.01±1.48 kg/m2, average Baseline Metabolic Rate (BMD) were 8643±924.06 (kJ), average Body Fat Percentage (%) were 12.86± .79%, average Fat Free Weight (FFM) were 71.59±7.37 kg, Visceral Fat Rating was 2.75±1.39, average right-left handgrip strength were 47.5±7.38-46.6±7.14 kg, average double foot jump with fixed-free hand values were 30.1±3.62 - 36.5±4.45 cm, average right-left hand visual reaction rate were 258.9±17.77 - 261.8±23.04 msec, average pro-agility agility test were 5.22±0.18 sec, and the average flexibility were 11.9±5.22 cm. As a result, physical and physiological characteristics of the Olympic Champion Turkish Deaf Men`s National Handball Team is compared to the evaluated literature; While the height, body weight, BMI, reaction speed, agility and body fat ratio values is parallel to other handball players, the flexibility and jumping values were found to be lower than other hearing-impaired athletes and handball players. In particular, grip strength values are higher than other hearing-impaired athletes, and parallel to the values of handball players.